Pengaruh Penambangan Pasir Terhadap Kondisi Sosial - Ekonomi, Fisik Dan Keluhan Kesehatan Masyarakat (Studi Kasus: Desa Pematang Kasih Kecamatan Mesuji, Ogan Komering Ilir) - Herda Sabriyah Dara Kospa; Anggelina Rosantika; Zaenal Mutaqin (Jurnal Tekno Global, 2021)
Sand mining in Indonesia with an open pit mining system in the river has been carried out for decades. In the past, the use of traditional tools such as hoes, shovels and cikrak with human power is a mining model that is widely available in rivers. However, with the increasing demand for river sand, mining using manual tools has began to be replaced by sand mining with a sand suction machine. It should be noted that initially the majority of the people in Pematang Kasih Village were farm laborers who earned income only when the harvest season arrived. The occurrence of an economic crisis in some people in the village, with limited job opportunities in Pematang Kasih Village caused them to look for alternative livelihoods in other sectors to meet their daily needs, one of which is sand mining. The purpose of this study was to determine the effect of sand mining activities on the socio-economic, physical and public health conditions in Pematang Kasih Village. This research conducted survey method and uses quantitative descriptive analysis. It is basically gave a positive impact in the form of increasing income for miners and the ease of fulfilling local sand materials at cheaper prices and short ordering times. Meanwhile, the negative impact felt by the community is mostly through the sand mining business which can result in environmental damage such as river pollution caused by the liquid waste, disturbance of health and safety of the population, air pollution in the form of dust and clean water pollution, as well as roads damaged by the sand transporting route that crosses the area around the population. Keywords: Sand Mining, Socio-Economic, Environmental Damage, Public Health